Anxiety in Hadith Perspective: A Study of Ihya’ Al-Sunnah Management - Sultani, Hikmawati; Ahmad, Arifuddin; Yahya, Muhammad (An-Nida', 2023)
The Nabi has paid great attention to the psychological state of his people and one of them is anxiety. Anxiety is a normal condition but if it occurs intensely and is not handled, it will have implications for a person's psychological and social life. Humans are fragile and weak creatures, so the apostle shared how to overcome anxiety through spiritual psychotherapy in the form of prayer. The purpose of the study is to explore the meaning of the hadith about anxiety. The type of research used is qualitative using the maudu'iy method. This research is based on the management of ihya' al-hadis which is based on the steps; a) input of hadith data c) output; and d) outcome. This study concludes that the textual interpretation of anxiety is interpreted as al-hamm which means anxiety, worry, unrest, and restlessness which always goes hand in hand with the word al-hazn (sadness). As for the intertextual hadith, anxiety is a feeling of being hit by worry, anxiety, and anxiety manifested from various mixed emotional processes that occur when a person is depressed and experiencing conflict or something that is not right. The contextual meaning; prayer for protection from Allah can be done in everyday life or when struck by anxiety. The output of this hadith is seen from the substantive (maqasid al-hadis) can be hajiyyah and even daruriyyah which is formally (al-sunnah al-nabawiyyah) in the form of qawliyyah. The outcome of this hadith is syumuliyyah and mahalliyah which can be applied by each person proportionally and even optimally. Abstrak: Rasulullah Saw., telah menaruh perhatian yang besar terhadap keadaan psikologis umatnya and salah satunya adalah anxiety atau kecemasan. Anxiety merupakan keadaan yang normal namun jika terjadi secara intens and tidak tertangani maka akan berimplikasi pada psikis seseorang and kehidupan sosialnya. Manusia adalah makhluk yang rentan rapuh and lemah, maka rasul sharing cara mengatasi anxiety melalui psikoterapi spiritual berupa doa. Tujuan penelitian ini adalah untuk menggali kandungan makna hadis tentang anxiety. Jenis penelitian yang digunakan adalah kualitatif dengan menggunakan metode maudu’iy (tematik). Penelitian ini didasarkan pada cara kerja manajemen ihya’ al-hadis yang berdasarkan pada langkah; a) input data hadis; b) proses interpretasi; c) output; and d) outcome. Penelitian ini berkesimpulan bahwa interpretasi secara tekstual anxiety dimaknai al-hamm yang beriringan dengan kata al-hazn (kesedihan). Secara intertekstual hadis anxiety merupakan perasaan dilanda kekhawatiran, kegelisahan, and kecemasan yang termanifestasikan dari berbagai proses emosi yang bercampur baur yang terjadi ketika seseorang seandg tertekan and alami pertentangan atau sesuatu yang tidak disenangi. Sedangkan makna kontekstual; doa permohonan perlindungan pada Allah dapat dilakukan dalam keseharian atau pada saat dilanda anxiety. Output hadis ini dilihat dari subtantif (maqasid al-hadis) dapat bersifat hajiyyah bahkan daruriyyah yang secara formatif (al-sunnah al-nabawiyyah) berbentuk qawliyyah. Outcome hadis ini bersifat syumuliyyah and mahalliyah yang dapat diterapkan oleh setiap personal secara proposional bahkan optimal.